2022
DOI: 10.3390/molecules27238331
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Smilax china L. Root Extracts against the Acne-Causing Bacterium, Cutibacterium acnes, and Its Active Compounds

Abstract: The root of Smilax china L. is used in traditional Korean medicine. We found that the Smilax china L. root extract has strong antimicrobial activity against two Cutibacterium acnes strains (KCTC 3314 and KCTC 3320). The aim of this study was to identify the beneficial properties of Smilax china L. extracts for their potential use as active ingredients in cosmetics for the treatment of human skin acne. The high-performance liquid chromatography (HPLC) and liquid chromatography-hybrid quadrupole time-of-flight m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The high-speed homogenization method which is convenient and efficient as compared to low-energy emulsification, because of its limitation as it provides less energy, was applied to overcome the obstacles and limitations of the conventional formulation [72]. In this technique, a homogenizer provided high energy to the mixture which was kept in it to lower the particle size.…”
Section: Discussionmentioning
confidence: 99%
“…The high-speed homogenization method which is convenient and efficient as compared to low-energy emulsification, because of its limitation as it provides less energy, was applied to overcome the obstacles and limitations of the conventional formulation [72]. In this technique, a homogenizer provided high energy to the mixture which was kept in it to lower the particle size.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, these components exert anti-inflammatory effects by suppressing the release of inflammatory cytokines, such as IL-6, IL-1β, and TNF-α, and TLR-mediated NF-κB, STAT, or MAPK signaling [ 52 , 53 , 54 , 55 ]. Moreover, gallic acid, quercetin, and kaempferol have been previously reported to possess anti-acne vulgaris effects [ 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ]. These reports indicate that gallic acid, fisetin, quercetin, and kaempferol may be closely associated with the favorable anti-acne effects of FRO.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, the hexane and methanol extracts exhibited pronounced inhibition against B. subtilis and S. aureus (Gram-positive) within the concentration range of 25,000 to 200,000 µg•mL −1 , surpassing the inhibitory potency of the ethylacetate extract. Conversely, all the extracts demonstrated comparatively lower antibacterial activity against Gram-negative bacteria, including E. coli, K. pneumoniae, P. It should be noted that the previously mentioned significant variations in MIC values found in the literature are also applicable to root extracts: Joo et al [49] reported that S. china root extracts exhibited strong antimicrobial activity (500 µg•mL…”
Section: Activity Of S Aspera and Other Smilax Spp Extractsmentioning
confidence: 93%